Do female directors will have impact on corporate performance? - Ting, Irene Wei Kiong; Wang, Wei-Kang; Lu, Wen-Min; Chen, Yun-Jung
The purpose of this study is to explore the influence of female directors on the corporate performance of Chinese banks and Taiwanese financial holding companies. The sample consists of 14 Chinese banks and 15 Taiwanese financial holding companies in 2010–2014. The empirical results show that the proportion of non-executive female directors and independent female directors have significant positive influence on corporate performance. The result shows that the higher the proportion of female directors is, the better off the corporate performance would be. There is robust evidence in the data to conclude that female directors in specific posts can influence a firm’s corporate performance.